Capital Budgeting of Risky Projects with "Imperfect" Markets for Physical Capital - Bogue, Marcus C.; Roll, Richard (Journal of Finance, 1974)
Marcus C. Bogue, Richard Roll, Capital Budgeting of Risky Projects with "Imperfect" Markets for Physical Capital, The Journal of Finance, Vol. 29, No. 2, Papers and Proceedings of the Thirty-Second Annual Meeting of the American Finance Association, New York, New York, December 28-30, 1973 (May, 1974), pp. 601-613